The function f(x) = x2 – 6x + 9 is shifted 5 units to the right to create g(x). What is g(x)? 3

A.g(x) = (x + 5)2 – 6(x + 5) + 9

B.g(x) = (x2 – 6x + 9) – 5

C.g(x) = (x2 – 6x + 9) + 5

D.g(x) = (x – 5)2 – 6(x – 5) + 9

Respuesta :

the answer is d, im pretty sure 

Answer:

D. [tex]g(x)=(x-5)^2-6(x-5)+9[/tex]

Step-by-step explanation:

The resulting function after shifting a function f(x),

a unit right = f(x-a),

a unit left = f(x+a),

Here, the given function,

[tex]f(x) = x^2 - 6x + 9-----(1)[/tex]

Thus, by the above statement,

After shifting f(x) by 5 unit right, the transformed function,

[tex]g(x)=f(x-5)[/tex]

[tex]\implies g(x)=(x-5)^2-6(x-5)+9[/tex]  ( From equation (1) )

Hence, option 'D' is correct.

ACCESS MORE